Corrections to "HTGCE: An Graph-Based and Classifier-Oriented Dimension Reduction Method for Multisource Heterogeneous Feature Tensors" - Gao, Tong; Chen, Hao; Chen, Wen (IEEE transactions on geoscience and remote sensing, 2022)
In the above article [1] , some errors appear in equations due to incorrect fonts. First, the matrix variables should be denoted by uppercase boldface letters, e.g., \boldsymbol{U}_{l}^{m} and \boldsymbol{S}_{g} . The vector variables should be denoted as lowercase boldface letters, e.g., c and c^{′} .